Restorative Justice Sebagai Solusi Over Capacity di Lembaga Pemasyarakatan Kelas II A Cilegon - Aslinda Aprilita Riski; H. Hasuri (Jurnal Interpretasi Hukum, 2025)
Overcapacity in Cilegon class IIA correctional institutions is a serious problem that has negative impacts, such as worsening the health conditions of inmates, increasing the potential for conflict, and decreasing the effectiveness of coaching programs. The solution that is starting to be implemented is a restorative justice approach, which emphasizes recovery for victims, accountability for perpetrators, and community involvement in resolving criminal cases. Even though the concept of restorative justice has been widely discussed in legal and policy literature, its implementation in the field still faces various challenges. This research aims to analyze the application of restorative justice as a solution in reducing the number of residents in Cilegon class IIA correctional institutions. This research method is empirical juridical legal research that focuses on the implementation of regulations in practice. The approach used is sociological juridical and analytical descriptive specifications. The data used is primary data and is supported by secondary data with qualitative data analysis. The application of rhetorical justice in resolving criminal cases experiences a major obstacle, namely the failure to reach an agreement between the victim and the perpetrator so that they have to resort to litigation in resolving a case which has an impact on overcapacity in correctional institutions. The results of the research show that resolving cases through restorative justice cannot be fully implemented to overcome the problem of overcapacity in class IIA Cilegon community institutions, however Cilegon city law enforcers always try to resolve cases using restorative justice.